Research of gifted children’s mathematical education in Lithuanian basic school - Sičiūnienė, Viktorija; Dargytė, Janina (Lietuvos matematikos rinkinys, 2010)
The amount of research on the recognition and education of children and young people gifted in mathematics is very little in Lithuania. Therefore, the article author’s used the data from national surveys 2005–2008 and attempted to identify gifted children using Item Response Theory approach. The following in article analyzing what is the selected children’s math achievement in school (trimester marks), how students themselves evaluate their abilities in mathematics, what is their homeenvironment, computer experience, how they feel at school and in the classroom, what are their attitudes to mathematics and its learning.
Keywords: gifted children in mathematics; the opinion about abilities in mathematics; aptitudes and marks; feel at school and in the classroom